Depressive symptoms and serum levels of vitamins B12 and folate in elderly from Florianópolis/SC: Epifloripa Elderly Study (Research, Society and Development, 2022)
Depression is characterized by symptoms of deep sadness and mood swings. Deficient levels of folate and vitamin B12 have been related to the development of depression, as they play key roles in the proper functioning of the brain. The aim of the study was to investigate the association between the serum concentration of vitamin B12 and folate and symptoms of depression in elderly people in southern Brazil. Data from the second wave of the population-based and household survey (EpiFloripa) were analyzed. A total of 590 elderly (≥60 years) participated in the collection of blood for biochemical analysis. The presence of symptoms of depression was assessed using the Geriatric Depression Scale (GDS-15) with a cut-off point ≥ 6. Vitamins B12 and folate were measured through biochemical tests. Binary Logistic Regression was used to analyze the association between the variable symptoms of depression and vitamins. 16.4% of the elderly had symptoms of depression, being more frequent in women, people with chronic disease and low education. The lower mean serum vitamin B12 does not explain the presence of symptoms of depression (OR= 1.000; CI: 0.999; 1.001). The lowest mean serum folate was associated in the crude analysis with the presence of symptoms of depression (OR= 0.931; CI: 0.886; 0.978) and was maintained after adjustment for control variables (OR= 0.937; CI: 0.888; 0.988). The highest mean serum folate is a protective factor for the occurrence of depressive symptoms. Although vitamin B12 has not been associated with symptoms of depression, maintenance of higher averages is recommended in the elderly.